Fertilization regime interacts with fall temperature in the nursery to determine the frost and drought tolerance of the Mediterranean oak Quercus ilex subsp. ballota - Heredia-Guerrero, Norberto; Oliet, Juan a; Villar-Salvador, Pedro; Benito, Luis F; Peñuelas, Juan L (Forest Ecology and Management, 2014)
Nitrogen fertilization in the nursery usually improves the transplanting performance of Mediterranean oaks. However, high N fertilization can reduce seedling stress tolerance, probably depending on the environmental conditions under which plants grow. We hypothesize that high N fertilization under mild fall conditions reduces cold and drought acclimation. To assess this hypothesis, we studied if fall temperature differences among cultivation locations influence the effect of N fertilization regime on cold and drought tolerance, N status and growth in the evergreen Mediterranean oak Quercus ilex subsp. ballota (Desf.) Samp. Plants were cultivated in two nurseries of distinct fall temperature conditions (mild and cold fall nurseries) under four fertilization regimes: Low and high N at constant rate (total N, 33 and 175mgseedling−1), high N at exponential rate (175mgNseedling−1) and fall N loading (89mgNseedling−1). Seedling water relations, survival to a −12°C frost and leaf soluble carbohydrates concentration were assessed three times in the fall, and shoot elongation was measured weekly through the fall. Moreover, seedling mass and N concentration were measured at the end of the fall. Fall loaded seedlings had the highest tissue N concentration, while seedling mass was highest in the high N constant and exponential fertilization regimes. Seedlings at the cold fall nursery concentrated more N but were smaller than seedlings at the mild fall nursery. Cessation of shoot elongation in the mild fall nursery occurred 1month later than in the cold location and high N exponentially-fertilized plants ceased shoot elongation later than the rest of fertilization treatments. Seedlings at the mild fall location had lower drought and cold tolerance than plants at the cold fall site. At mid fall, exponential fertilization at the mild nursery reduced seedling frost and drought tolerance, but treatment differences vanished at the end of the fall. In contrast, fertilization regime did not affect either cold or drought tolerance of seedlings at the cold fall nursery. Across dates and nurseries, frost survival was positively related to leaf soluble carbohydrates concentration and dry weight fraction. Beside, degree of cold acclimation decreased with shoot elongation cessation date and increased with leaf soluble carbohydrates concentration, suggesting a link between shoot growth activity, soluble carbohydrates, and frost tolerance. We conclude that Q. ilex subsp. ballota hardening is reduced by high N exponential fertilization mainly under mild fall conditions, while fall loading and constant low N fertilization did not affect hardening.
Keywords: Cold acclimation; Hardening; nitrogen; Nutrient loading; Osmotic potential; Soluble carbohydrate

Foliar absorption and root translocation of nitrogen from different chemical forms in seedlings of two Mediterranean trees - Uscola, Mercedes; Villar-Salvador, Pedro; Oliet, Juan; Warren, Charles R (Environmental and Experimental Botany, 2014)
Along with root uptake, plants can also absorb N through leaves. There are few comparative studies on the foliar absorption of N from different chemical forms of N in forest tree species. We compared the foliar N absorption capacity in seedlings of two forest trees widespread in the Mediterranean basin, Quercus ilex and Pinus halepensis. Plants were sprayed with the following individual N forms at 40mM N: 15N-nitrate (NO3−), 15N-ammonium (NH4+), 15N-urea or 13C and 15N dual-labeled glycine. Cuticular conductance was used as a surrogate of cuticle permeability to water. Q. ilex had higher N foliar absorption than P. hapelensis. Neither cuticular conductance nor shoot surface area explained N differences in absorption rate between species, which were instead likely linked to differences in stomatal density and presence of trichomes. In both species, foliar N absorption rate and N recovery differed among N forms: urea>NH4+≥glycine≥NO3−. Differences in N absorption rate among N forms were correlated with their physico-chemical properties. The strong positive relationship between 15N and 13C uptake together with detection in shoots of intact dual-labeled glycine (measured by gas chromatography–mass spectrometry), indicated that a significant fraction of glycine was absorbed intact by the seedlings. In both species, higher cuticular conductance was related to faster N absorption from all forms except NO3−. Cuticular conductance had a stronger effect on N absorption from urea and NH4+ than N absorption from glycine, and the effects were more intense in Q. ilex than in P. halepensis. This suggests that variations in cuticle permeability in both species are determined by different mechanisms and that each N form was differently affected. Absorbed N was rapidly translocated to roots, with a larger proportion of N from organic forms being translocated than N from inorganic forms. Foliar fertilization increased plant N content, especially in urea fertilized plants, but direct foliar absorption only explained up to 10% of N content increase. This study demonstrates that two important Mediterranean forest tree species can absorb through their leaves both, inorganic and organic N forms. This has important ecological and applied implications, because all chemical forms of N are present in natural N deposition. Also results show that foliar N fertilization can play an important role for seedling N nutrition, and that the effect will have different impacts depending on the species.
Keywords: Ammonium-nitrate; Cuticular conductance; Glycine; Pinus halepensis; Quercus ilex; Urea

Nitrogen form and concentration interact to affect the performance of two ecologically distinct Mediterranean forest trees - Uscola, Mercedes; Oliet, JuanA.; Villar-Salvador, Pedro; Díaz-Pinés, Eugenio; Jacobs, DouglassF. (European Journal of Forest Research, 2014)
Most studies examining inorganic N form effects on growth and nutrition of forest trees have been conducted on single species from boreal or temperate environments, while comparative studies with species from other biomes are scarce. We evaluated the response of two Mediterranean trees of contrasting ecology, Quercus ilex L. and Pinus halepensis Mill., to cultivation with distinct inorganic N forms. Seedlings were fertilized with different NH4 (+)/NO3 (-) proportion at either 1 or 10 mM N. In both species, N forms had small effects at low N concentration, but at high N concentration they markedly affected the plant performance. A greater proportion of NH4 (+) in the fertilizer at high N caused toxicity as it reduced growth and caused seedling death, with the effect being greater in Q. ilex than in P. halepensis. An increase in the proportion of NO3 (-) at high N strongly enhanced growth relative to low N plants in P. halepensis but had minor effects in Q. ilex. Relatively more NH4 (+) in the fertilizer enhanced plant P concentration but reduced K concentration in both species, while the opposite effect occurred with NO3 (-), and these effects were enhanced under high N concentration. We conclude that species responses to inorganic N forms were related to their ecology. P. halepensis, a pioneer tree, had improved performance with NO3 (-) at high N concentration and showed strong plasticity to changes in N supply. Q. ilex, a late successional tree, had low responsiveness to N form or concentration.
Keywords: ammonium; ecophysiology; Growth; nitrate; Pinus halepensis; Quercus ilex

Facilitation of Quercus ilex in Mediterranean shrubland is explained by both direct and indirect interactions mediated by herbs - Cuesta, Bárbara; Villar-Salvador, Pedro; Puértolas, Jaime; Rey Benayas, José M.; Michalet, Richard (Journal of Ecology, 2010)
1. Competitive and facilitative interactions shape plant communities. Whereas a number of studies have addressed competition and direct facilitation among plants in dry ecosystems, indirect facilitation has received little attention. 2. We investigated the relative importance of direct and indirect facilitation by the nurse plant Retama sphaerocarpa on late-successional Quercus ilex seedlings mediated by herb suppression in a Mediterranean shrubland in 2006 and 2007. We also studied whether facilitation outcome depended on the size of the facilitated seedlings. 3. A field experiment was carried out to test the effect of (i) position of Q. ilex seedling with respect to shrub canopy (under shrubs or in gaps), (ii) herb competition (presence or absence), and (iii) seedling size. 2006 was an average rainfall year while 2007 had a much more humid spring and a dryer summer than 2006. 4. In both years, nurse shrubs reduced seedling mortality whereas herbs increased it. In the average rainfall year, seedling mortality under shrubs was unaffected by herbs whereas in gaps it was significantly higher in presence of herbs. This showed that the nurse shrub indirectly facilitated the seedlings by reducing the competitive capacity of herbs. Conversely, facilitation was predominately direct during the humid spring and dry summer year since herbs hindered seedling survival similarly under the nurse shrub and in gaps. The nurse shrub directly facilitated the seedlings by reducing seedling photoinhibition and water stress. 5. Improvement of environmental conditions by Retama benefited smaller seedlings but not larger seedlings since the nurse shrub reduced mortality of smaller seedlings relative to that in gaps, but this effect was not observed for larger seedlings. This indicates that individuals within a seedling population may not have the same response to facilitation. 6. Synthesis. Both indirect and direct facilitation are important mechanisms for Q. ilex regeneration in Retama shrubland and their importance seems to vary with climatic conditions. Indirect facilitation by release of herb competition under nurse shrubs is important in years of dry springs when competition between nurse shrubs and herbs is high, whereas direct facilitation mediated by microclimate amelioration increases with summer aridity.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: chlorophyll fluorescence; herb competition; Quercus ilex; retama sphaerocarpa; seedling size; water potential

Remobilization of acorn nitrogen for seedling growth in holm oak (Quercus ilex), cultivated with contrasting nutrient availability. - Villar-Salvador, Pedro; Heredia, Norberto; Millard, Peter (Tree physiology, 2010)
The relative contribution of nitrogen (N) reserves from seeds or uptake by the roots to the growth and N content of young seedlings has received little attention. In this study, we investigated the contribution of N from the acorn or uptake by the roots to the N content of holm oak (Quercus ilex L.) seedlings and determined if remobilization of acorn N was affected by nutrient availability in the growing media. Q. ilex seedlings were cultivated for 3 months, until the end of the second shoot flush of growth, with three N fertilization rates: 8.6 mM N, 1.4 mM N or no fertilization. Fertilizer N was enriched in (15)N. Between 62 and 75% of the N contained in high and low fertilized seedlings, respectively, at the end of the second flush of growth was derived from the acorn. However, the dependence on acorn N was greater during the early root growth and first shoot flush of growth and decreased during the second shoot flush of growth, with root uptake contributing 32-54% of plant new N in this latter developmental stage in high and low fertilized plants, respectively. Fertilization rate did not affect the amount of N taken up during the earliest developmental stages, but it increased it during the second shoot flush of growth. Fertilization increased the mass of the shoot segment formed during the second shoot flush of growth and reduced the root mass, with no effect on whole plant growth. Remobilization of acorn N was faster in unfertilized plants than in fertilized plants. It is concluded that the holm oak seedlings depend greatly upon acorn N until the end of the second shoot flush of growth, that significant root N uptake starts at the beginning of the second shoot flush of growth and that acorn N remobilization is a plastic process that is accelerated under extremely low substratum nutrient content.
Keywords: germination; nitrogen; Nitrogen Isotopes; Nitrogen Isotopes: metabolism; Nitrogen: metabolism; Quercus; Quercus: growth & development; Quercus: metabolism; Seedling; Seedling: growth & development; Seedling: metabolism; Seeds; Seeds: metabolism; Soil

Why do large, nitrogen rich seedlings better resist stressful transplanting conditions? A physiological analysis in two functionally contrasting Mediterranean forest species - Cuesta, Bárbara; Villar-Salvador, Pedro; Puértolas, Jaime; Jacobs, Douglass F.; Rey Benayas, José M. (Forest Ecology and Management, 2010)
We analysed the physiological bases that explain why large and high nitrogen (N) concentration seedlings frequently have improved survival and growth relative to small seedlings in Mediterranean woodland plantations. Large seedlings of Aleppo pine (Pinus halepensisMill.) and holm oak (Quercus ilex L.) with high N concentration (L+), and small seedlings with either high (S+) or low (S−) N concentration, were planted on two sites of different weed competition intensity that created contrasting stress conditions. Seedling survival, growth, gas exchange, N remobilization (NR) and uptake (NU), and water potential were assessed through the ﬁrst growing season. Weeds reduced survival and growth, but seedling response to weed competition varied among phenotypes and between species. At the end of the ﬁrst growing season, L+ Aleppo pine seedlings had higher survival than both small seedling types in presence of weeds but no differences were observed in absence of weeds. Mortality differences among phenotypes occurred in spring but not in summer. L+ Aleppo pines grew more than small Aleppo pines independently of weed competition. No holm oak seedling type survived in presence of weeds and no mortality differences among phenotypes where observed in absence of weeds, although L+ holm oak seedlings grew more than small seedlings. Mortality and growth differences in Aleppo pine were linked to marked physiological differences among phenotypes while physiological differences were small among holm oak phenotypes. L+ Aleppo pines had greater root growth, gas exchange, NR, and NU than small seedlings, irrespective of their N concentration. Seedling size in Aleppo pine had a greater role in the performance of transplanted seedlings than N concentration. The functional differences among oak phenotypes were small whereas they were large in pine seedlings, which led to smaller differences in transplanting performance in holm oak than in pine. This suggests that the nursery seedling quality improvement for planting in dry sites could depend on the species-speciﬁc phenotypic plasticity and functional strategy. Improved transplanting performance in large Aleppo pine seedlings relative to small seedlings was linked to greater gas exchange, root growth and N cycling.
Keywords: competition; Nitrogen remobilization; photosynthesis; Pinus halepensis; Quercus ilex; Root growth; Stomatal conductance; Survival; water potential